Avaliação da competitividade do varejo: estudo de caso sobre o setor de distribuição de jornais e revistas - Azevedo, Isa Gomes da Costa (2003)
The proposal of the study is to contest periodical boards in the competitive environment of the retail. Looking into their degrees of competitiveness to the extent which shows the determinative forces of the competitive advantages based in the theory developed for Porter (1985) and of the relations of existing logistic partnerships in the sector under the optics of the Castanha studies (1999). This study demonstrates that the main forces of the industry to be acted upon are in the sector of the suppliers in the special the delivereries of periodicals and magazines. Due to its importance as the main link of the chain of supplying between the publishing companies; the substitute products lead to the high index of competitiveness found in the middle class. Which category of commercialized goods and which consumers prevail in the typical newsstand? Decline in sales can be attributted to customers contacting the publishing companies and arranging to purchase their books and magazines direct from the publisher (delivery service of periodicals). The results of the research demonstrates also thet the magazine stores do not work in partnership according to the model considered for Castanha (1999) of strategical nets. And yes with traditional commercial partnerships using large supply chains. The newstands impersonate the retail establishment the deliverers function as deliverer and wholesaler simultaneously. The study demonstrates that the stores do not explore their resources well; especially in regards to the employees with vast amounts of knowledge on knowledge on prepared receiving techniques from venders, service contracts, and on the products that build buisness. A great advantage is lost between friendly sales persons and the purchaser. Customers appreciate courteous sales persons and are more likely to repeat their shopping experience as well as pass on this positive experience to their friends